A Systems study on the Makati Central Post Office - Ericta, Jean.; Mag-iba, Arlene Gay.; Matias, Ma. Belinda; Raroque, Victor; Reyes, Armando (Diliman, Quezon City College of Engineering, 1991)
This is a systems study of the Makati Central Post Office. The study aims to improve the quality of postal services offered by the MCPO, particularly, the guaranteed 24-hour delivery of first class mail. Although the MCPO authorities claim that this goal has been achieved in normal circumstances or during adverse situations (wherein improvisation is applied), the system may still be improved. Several areas for study have been cited. These are: 1) Level of manpower resources; 2) Worker allocation; 3) Mail collection routing; 4) Capacity to cope up with increasing volume of mail; 5) Financial independence from the Central Office; 6) Adequacy of the level of supplies and equipment; 7) Postal management; 8) Public adherence to the standard postal format; and, 9) Mail processing operations. These were analyzed by using pertinent data collected from files, records, or interviews. The present system was evaluated and then problems were enumerated. Alternatives were generated by research and IE fundamentals on methods study, shortest route method (OR) and capacity planning. From these alternatives, a number was selected based on criteria, and combined to come up with the alternative system design. Secondary data gathering was limited by the following: 1) MCPO has no records regarding costs incurred because these are kept by the CO; 2) MCPO has no records of arrival patterns and of the different kinds of mail; 3) Some of the mail volume recorded are aggregate sums (such as, the number of SSS and GSIS checks is under registered incoming letterposts); 4) The volume of mail from each collection point is not recorded anymore. They used to record this along with the time it takes from one collection to another. At present, no such records are taken; and, 5) There is no specific allocation of manpower because casuals are assigned to different sections. Any important secondary data that could not be obtained were extracted from interviews with MCPO personnel. The present system of the MCPO has been documented under the mentioned objectives and limitations. The organizational structure comprised of the administrative and operational divisions were studied along with their linkages to other external units with whom mail transactions take place. Upon evaluation of the system, the following problems were noted: 1) There is no clear-cut definition of functions and assignment of jobs for the MCPO employees; 2) There is an inadequate manner of employees to satisfy the manpower need of MCPO to the CO on personnel allocation hampers their work efficiency; 3) The dependence of the MCPO to the CO on personnel allocation hampers their work efficiency; 4) Mail processing efficiency can be affected by repetitive and exhausting work methods; 5) Mail routing scheme is not proven as the shortest route; 6) Provided postal funds do not satisfy the needs of the facility; 7) The MCPO experiences supply and equipment shortages due to centralized allocation by the Central Office; 8) Some work areas are congested; 8) Some work areas are not properly lit or ventilated; 9) There is an absence of a good and consistent effort to carry out public relation and information programs; 10) Judgments and managerial initiative is hampered by dependence upon the Central Office; and 11) There are no standards enforced on envelope sizes, ZIP codes, etc. These problems were categorized into: a) Administrative ? pertains to decision making, finances, supply and equipment shortage, personnel, PR; b) Operational ? pertains to work conditions, product processing, methods of processing. One alternative for the administrative problem is to decentralize the functions covering financing, decision-making, supply and equipment, and personnel. The schedule of operations can be greatly improved if the Central Office did not have such a great control on these matters. The MCPO would operate on its own set of policies. Not all activities will be decentralized. Sorting will still be conveniently centralized in the CO where a larger mail volume can be sorted. Operational problems stem from 3 areas (Mail processing, Mail movement within the Post Office and Mail transport to and from the Post Offices). Mechanization can alleviate problems in the first two categories. The MCPO can choose from a practically mechanized design (only for sorting and mail movement operations) or an integrated mechanical design (total mechanization). A number of machines were enumerated for each mail processing operation. Intra-plant traffic management is generally aided by conveyors. Mail preparation (culling, facing and cancelling) had various versatile machines of different abilities and capacities. Mail sorting machines were classified into: a) Keysorting Machines - a human operator punches a code in the machine which in turn automatically sends it to its destined pigeonhole; b) Code sorting machine - similar to the keysort machine but aided by computer memory, lessening load on operator memory; c) Character recognition - destination read and sorted totally by machine. Between a partially mechanized design and a totally mechanized design (composed o machines of matched capacities), one will be selected based on the following criteria: *Cost, *Adaptability, *Impact on productivity, *Operational safety and *Degree of consequential changes upon implementation. For the recommendations, implementation time is divided into short and long term. Short Term Plans: 1) Purchase of ergonomically designed chairs and sorting tables; 2)Use of color coded sack; 3) Use of intra-plant transport equipment such as conveyor belts; 4) Encourage early mailing; 5) Stratification of first class mail; 6) Use of carbonized receipts; 7) Restoration of the elevator for mail transport and personnel use; and, 8)Apply the shortest route study. Long Range Plans: 1) Office automation wherein computers are used in processing, generation and storing of data; 2) Partial mechanization of the office; and, 3) Decentralization. The new MCPO is foreseen to be a more efficient public service facility with innovations in its administrative structure, work environment, and mail processing operations. It will be handled by a government owned corporation and be financially independent from the Central Office. This corporation will find other sources of financing such as bonds for modernization to be able to support the operations of the facility. The MCPO will likewise be independent when it comes to employee allocation, decision-making, supplies and equipment. Therefore, new departments will be created as a result of the decentralization process. Public information drives will be launched to encourage standardization. People are envisioned to mail early and make use of ZIP codes and envelopes of standard sizes. There will be coordination and cooperation established between the MCPO and the public to gain support for mutual benefits from speedier mail processing and delivery. The office will do its part by using shortest routes to pick up mail. For the sorting and transport operations, machines will be used for faster processing. The remaining manual operations will be improved by ergonomic fixtures for workers and proper allocation of manpower by capacity planning.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 155 : Industrial Systems Design
Keywords: Makati Central Post Office; System design